2021
DOI: 10.1007/s11469-021-00681-1
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Tool for Exercise Addiction: The Psychometric Properties of the Italian Exercise Addiction Inventory

Abstract: Exercise addiction is characterized by morbid pattern of behavior which may have negative psychological consequences, seriously compromising the lives of those affected. The Exercise Addiction Inventory (EAI) is one of the most used psychometric instruments for assessing the risk of exercise addiction and has been translated into a number of languages. However, it has never been psychometrically validated in Italian. Therefore, the purpose of the present study was to test the psychometric properties of the EAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…The outcomes of the present study showed that the Persian versions of EAI and EAI-Y both had unidimensional structure and good internal consistency when analyzed using both the CTT and Rasch techniques. The unidimensional structure was comparable to the proposed structure in the original English version (Terry et al, 2004) as well as other translated versions in non-English countries such as Mexico (Salazar et al, 2021), Italy (Gori et al, 2021), Denmark (Lichtenstein et al, 2012), and Hungary (Mónok et al, 2012). Additionally, the invariance of items in the Persian version across gender and age is consistent with crosscultural studies conducted in the United States, the United Kingdom, Spain, Denmark, and Hungary (Griffiths et al, 2015).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The outcomes of the present study showed that the Persian versions of EAI and EAI-Y both had unidimensional structure and good internal consistency when analyzed using both the CTT and Rasch techniques. The unidimensional structure was comparable to the proposed structure in the original English version (Terry et al, 2004) as well as other translated versions in non-English countries such as Mexico (Salazar et al, 2021), Italy (Gori et al, 2021), Denmark (Lichtenstein et al, 2012), and Hungary (Mónok et al, 2012). Additionally, the invariance of items in the Persian version across gender and age is consistent with crosscultural studies conducted in the United States, the United Kingdom, Spain, Denmark, and Hungary (Griffiths et al, 2015).…”
Section: Resultssupporting
confidence: 74%
“…Since then, a number of validation studies have confirmed the psychometric properties of the EAI in different cultures and sport settings. For example, the EAI has been found to be an adequate and reliable instrument in Mexico (Salazar et al, 2021), Spain (Alías-García et al, 2013, Hungary (Mónok et al, 2012), Italy (Gori et al, 2021). In a series of studies in the Danish context, Lichtenstein et al (2012Lichtenstein et al ( , 2014Lichtenstein et al ( , 2016 found good reliability and construct validity for the EAI among samples of Danish elite athletes, football players, fitness exercisers, and cross-fitters (a mix of aerobic and anaerobic exercise).…”
Section: The Exercise Addiction Inventorymentioning
confidence: 99%
“…Therefore, emphasis was placed on the experiences with caregivers and insecure attachment, and negative developmental environments were considered risk factors for addiction occurrence [ 8 , 9 , 10 , 11 , 12 ]. These attachment failures might represent the source of childhood traumatic experiences [ 13 ] and deficits in emotion regulation skills [ 14 ], with difficulty modulating, processing, and communicating emotions (i.e., alexithymia; [ 15 ]) as a consequence; this condition, in turn, could lead to a defensive withdrawal into dissociated mental states to cope with painful emotions [ 16 , 17 , 18 , 19 , 20 , 21 ], which has been associated both theoretically and empirically with addictive behaviors [ 22 , 23 , 24 , 25 ]. However, the escape into the temporary retreat of substance use or addictive behavior further hinders the possibility of developing regulatory skills [ 4 ] by pushing toward an impulsive and compulsive search for immediate (but not lasting) gratification and making the substance or behavior as central in the individual’s life with recurrent and persistent thoughts, therefore facilitating the perpetuation of the addiction and, ultimately, hindering the treatment [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drive for leanness refers to the tendency to extreme aspiration of being thin and being afraid of gaining weight, as well as a particular recognition of diet concerns [ 33 ]. It has frequently been found to be a significant predictor of compulsive exercise in cases where losing weight is one of the main personal goals [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%